2021
DOI: 10.3390/antibiotics10080943
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Consumption among 66 Acute Care Hospitals in Catalonia: Impact of the COVID-19 Pandemic

Abstract: Background: Antimicrobials have been widely used during the COVID-19 pandemic. This study aimed to analyze the impact of the COVID-19 pandemic on the antimicrobial consumption of 66 hospitals in Catalonia. Methods: Adult antibacterial and antimycotic consumption was calculated as defined daily doses (DDD)/100 bed-days and DDD/100 discharges. Firstly, overall and ICU consumption in 2019 and 2020 were compared. Secondly, observed ICU 2020 consumptions were compared with non-COVID-19 2020 estimated consumptions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 33 publications
5
39
2
1
Order By: Relevance
“…In addition, the high use of vitamins and zinc is in line with current national guidelines in Bangladesh (Box 1). However, there were concerns with the high empiric use of antibiotics (Table 2) despite, as mentioned, only a limited number of patients across ages have concomitant fungal or bacterial infections [62][63][64][65][66][67][68][69] . In addition, concerns with overuse are documented in the current national guidelines (Box 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the high use of vitamins and zinc is in line with current national guidelines in Bangladesh (Box 1). However, there were concerns with the high empiric use of antibiotics (Table 2) despite, as mentioned, only a limited number of patients across ages have concomitant fungal or bacterial infections [62][63][64][65][66][67][68][69] . In addition, concerns with overuse are documented in the current national guidelines (Box 1).…”
Section: Discussionmentioning
confidence: 99%
“…Having said this, we are aware of the high use of antimicrobials in hospitals including intensive care units in treating patients with COVID-19 despite only a limited number of patients have concomitant fungal or bacterial infections [62][63][64][65][66][67][68][69] . This includes hospitals in Bangladesh 70,71 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore antimicrobial monitoring use in the case of the pandemic is crucial to identify concerning signs of misuse or overuse. Studies conducted in several countries found an increase in antimicrobial consumption in ICUs during the pandemic (Guisado-Gil et al, 2020;Rawson et al, 2020;Grau et al, 2021b;Ng et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Barrier precautions, increased focus on hygiene, environmental cleaning, patient isolation and the increased use of PPE, have certainly played an important role in preventing C. difficile transmission, despite the increased/inappropriate use of broad-spectrum antibiotics, with about 70% of patients with COVID-19 subjected to antibiotic therapy mainly for the suspected acquisition of secondary bacterial infections [ 36 , 37 ]. However, it has to be considered that some antibiotics, such as azithromycin, are more extensively used compared with others for treatment of COVID-19 patients [ [38] , [39] , [40] ]. Although treatment with any antibiotic may precede the development of CDI, certain antibiotic classes have higher rates of association and, in addition, the associated CDI risk can be different within the same class [ 41 ].…”
Section: And the Covid-19 Pandemicmentioning
confidence: 99%